Endoscopic ultrasound-guided choledochoduodenostomy using a lumen apposing metal stent for acute cholangitis - Vasile Sandru; Mădălina Ilie; Oana Plotogea; Bogdan Silviu Ungureanu; Adina Stoica; Dan Ionut Gheonea; Gabriel Constantinescu (Turkish Journal of Gastroenterology, 2019)
We present the case of a 51-year-old woman with a history of uterine cancer who presented to the emergency room with a clinical picture of acute cholangitis. An abdominal ultrasound and a computed tomography scan were performed, revealing a gigantic lymphadenopathy mass compressing the common bile duct and the duodenum. After failure to perform an endoscopic retrograde cholangiopancreatography (ERCP) due to a modified anatomy, we performed an endoscopic ultrasound-guided choledochoduodenostomy (EUS-CDS) and placed a Hot AXIOS 10Fr/10 mm stent with efficient biliary drainage. In addition, we inserted a duodenal uncoated 120/22 mm expandable metallic stent. EUS-CDS presents a valid alternative in patients with failed ERCP and should be considered as an important option for rapid biliary decompression in patients with acute cholangitis. Cite this article as: Sandru V, Ilie M, Plotogea O, et al. Endoscopic ultrasound-guided choledochoduodenostomy using a lumen apposing metal stent for acute cholangitis. Turk J Gastroenterol 2018; 29: 511-4.